DOES ENTREPRENEURSHIP EDUCATION MATTER IN STUDENT’S ENTREPRENEURIAL INTEREST? - Widodo, Wulan; Mawardi, M. Kholid; Afrianty, Tri Wulida (FIA UB, 2022)
One of the entrepreneurs' roles in a country is to increase national economic development. The importance of entrepreneurship is that it's able to reduce unemployment by creating jobs. One of the driving factors of entrepreneurial growth in a state is the role of university through entrepreneurship education. Higher education as an educational institution plays an important role in developing state economy by shaping the students and giving birth to entrepreneurs. Universities are responsible in educating and providing entrepreneurial abilities to their students in order to increase interest in entrepreneurship. This study focuses on examining the relationship between entrepreneurial traits, entrepreneurial skills, and contextual factors on motivation and their influence on entrepreneurial interest. The population in this study were undergraduate students from the 2017 and 2018 batches of Universitas Brawijaya and asample of 387 respondents was obtained. The use of analysis with SEM-PLS proves that entrepreneurial traits, entrepreneurial skills, and contextual factors have a positive and significant effect on motivation and entrepreneurial interest. However, this study found that motivation had no significant effect on entrepreneurial interest. In future research, it is expected to be able to develop research by adding other variables and indicators so that it is more varied and can add research findings, especially in the field of entrepreneurial interest.